Long-term negative emotional outcomes of warzone TBI. Issue 6 (22nd July 2020) - Vasterling, Jennifer J.; Aslan, Mihaela; Proctor, Susan P.; Ko, John; Leviyah, Xenia; Concato, John
Abstract: Objective: Many veterans of the Iraq and Afghanistan Wars have experienced traumatic brain injury (TBI). Although prior work has examined associations between TBI and development of psychiatric syndromes, less is known about associations between TBI and component emotions constituting these syndromes, especially in the long term. The purpose of this study was to examine the long-term emotional consequences of deployment-related TBI. Methods: As part of VA Cooperative Studies Program #566, we assessed a sample of n  = 456 US Army soldiers prior to an index deployment to Iraq, and again an average of 8.3 years ( SD  = 2.4 years) after their deployment for a long-term follow-up assessment. In this report, we used adjusted regression analyses to examine the relationship of deployment TBI to depression, anxiety, and stress symptom severity measured at the long-term follow-up assessment. A structured interview was used to determine TBI history; the Depression, Anxiety, and Stress Scale, 21-item version (DASS-21) was used to determine emotional status at the follow-up evaluation. Results: Warzone TBI events, particularly when greater than mild in severity, were independently associated with depression, anxiety, and stress severity at long-term follow-up, even after taking into account variance attributable to pre-deployment emotional distress and war-zone stress. Post-hoc analyses did not detect independent associations of either number of events or injury mechanism with outcomes. Conclusions: These findings highlight the potentially enduring and multi-faceted emotional effects of deployment TBI, underscoring the need for early assessment of negative affectivity in warzone veterans reporting TBI.